2022
DOI: 10.20517/cdr.2022.83
|View full text |Cite
|
Sign up to set email alerts
|

New insights for drug resistance in metastatic castration-resistant prostate cancer

Abstract: Prostate cancer is the most common cancer and is the second leading cause of cancer-related deaths among men in the United States. Androgen deprivation therapy (ADT) is the standard treatment for advanced-stage prostate cancer; however, this treatment eventually fails, leading to an incurable disease subtype known as metastatic castration-resistant prostate cancer (mCRPC). There are several molecular mechanisms that facilitate the development of mCRPC engaging androgen receptor (AR) growth axis, including AR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…h, i). This is in line with the hypothesis that prolonged exposure to ATTs can give rise to aggressive subtypes in response to treatment [85][86][87] . The expression pattern of a gene set of 'efflux transmembrane transporters' matched most closely Kendall's tau 0.93) the predicted risk ranking of the clusters (Fig.…”
Section: Phenotype Algebra Enables Subclonal Grading Of Metastatic Pr...supporting
confidence: 89%
“…h, i). This is in line with the hypothesis that prolonged exposure to ATTs can give rise to aggressive subtypes in response to treatment [85][86][87] . The expression pattern of a gene set of 'efflux transmembrane transporters' matched most closely Kendall's tau 0.93) the predicted risk ranking of the clusters (Fig.…”
Section: Phenotype Algebra Enables Subclonal Grading Of Metastatic Pr...supporting
confidence: 89%
“…Despite significant improvements in the treatment of prostate cancer (PCa), patients with advanced disease will ultimately progress to metastatic castration-resistant prostate cancer (mCRPC) [ 1 , 3 ]. While various drugs, including docetaxel (DTX), the first-line therapy for mCRPC, initially lead to disease regression, resistance to these drugs ultimately renders mCRPC incurable [ 2 , 4 ]. Therefore, understanding the mechanisms of drug resistance and identifying new therapeutic targets remain crucial in delaying or reversing the progression of CRPC.β-arrestins, including β-arrestin1 and β-arrestin2, are identified as negative regulators of G-protein-coupled receptor (GPCR) signaling in initial.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel (DTX) has been the mainstay of chemotherapy for PCa and is the first drug to improve overall survival in CRPC patients. However, most patients treated with DTX eventually resist the drug, leading to refractory disease and disease recrudescence [ 2 4 ]. Therefore, it remains a significant challenge to identify the underlying mechanisms of DTX resistance and improve clinical outcomes for patients with CRPC.β-arrestin2 is a negative regulator of G-protein-coupled receptor (GPCR) signaling and plays an important role in cancer progression by serving as an adaptor to guide distinct pathway signals [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most PCa progress to the castration-resistance stage with androgen deprivation therapy (ADT) and/or androgen receptor signaling inhibitors [3]. Patients of this cancer stage develop primary or secondary resistance to androgen-or androgen receptor-targeted agents which are associated with multiple underlying mechanisms [4][5][6][7]. It is also reported that incidence of PCa is associated with germline mutations and polymorphisms of AR gene [8].…”
Section: Introductionmentioning
confidence: 99%